2020
DOI: 10.22219/mej.v4i2.12834
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Students 'Mathematic Ability in Using Open Ended Teaching Materials on Class VII Function Relations Materials

Abstract: This study aims to describe students' written mathematical communication skills in using open ended-based teaching materials on class VIII function relations material. The type of research used is descriptive qualitative. The research subjects were 5 students of class VIII E, SMP Negeri 12 Malang. Data collection techniques in this study in the form of tests and interviews. Research results obtained by students in the category of high mathematical communication skills have the ability to convert questions into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This study's findings reveal that some learners were able to use a correct scale and drew the correct diagram. These results show that these learners exhibit all the graphical efficacies according to Wulandari et al (2020) because they are able to convert mathematical information into graphical functions. Furthermore, these results are inconsistent with Angra and Gardener (2018) who found that learners find difficulty in graph construction and identifying the correct scale, labelling and scaling the axes.…”
Section: Correct Scale and Correct Graphmentioning
confidence: 71%
See 1 more Smart Citation
“…This study's findings reveal that some learners were able to use a correct scale and drew the correct diagram. These results show that these learners exhibit all the graphical efficacies according to Wulandari et al (2020) because they are able to convert mathematical information into graphical functions. Furthermore, these results are inconsistent with Angra and Gardener (2018) who found that learners find difficulty in graph construction and identifying the correct scale, labelling and scaling the axes.…”
Section: Correct Scale and Correct Graphmentioning
confidence: 71%
“…In studying trigonometric functions, learners are expected to be able to draw, use and interpret graphs during problem-solving (Halim, et al, 2023). According to Wulandari et al (2020), learners exhibit graphical efficacy if they are able to convert mathematical information into graphical functions. This study draws from and concurs with Yusrina et al (2020) who pointed out that learners exhibit graphical efficacy when they are able to draw the graph from the given equation and are able to interpret a drawn graph.…”
Section: Introductionmentioning
confidence: 99%
“…This study used snowball sampling as a subject-taking technique (Andriani et al, 2021) Pratiwi et al, 2020;Wulandari et al, 2020). Data analysis was performed in the data reduction, presentation, conclusion, and verification stages.…”
Section: Methodsmentioning
confidence: 99%